Centimeter-size square 2D layered Pb-free hybrid perovskite single crystal (CH3NH3)2MnCl4 for red photoluminescence. Issue 27 (18th June 2019) - Cheng, Xiaohua; Jing, Lin; Yuan, Ye; Du, Songjie; Yao, Qing; Zhang, Jie; Ding, Jianxu; Zhou, Tianliang
Abstract : Centimeter-size 2D layered Pb-free (CH3 NH3 )2 MnCl4 single crystal was grown by using different ways and proved to have good luminous via fabricating LED device. Abstract : Due to their excellent luminescent properties such as high stability, narrow band emission, and strong luminescence, hybrid organic–inorganic lead perovskites have great potential for application in optoelectronic devices. Compared to their conventional 3D counterparts, 2D perovskites exhibit enhanced moisture stability. Moreover, with the enhancement of exciton binding energy and limitation of charge carriers, 2D layered perovskites are considered ideal candidate materials for efficient light-emitting diodes (LEDs). However, hybrid organic–inorganic lead perovskites contain highly toxic Pb, which is considered as a major environmental pollutant and health hazard. Therefore, the further larger-scale applications are limited. Thus, exploiting the impressive properties and practical applications of 2D layered structure Pb-free hybrid organic–inorganic perovskites in the LED field is necessary. In the present work, a centimeter-size square 2D layered Pb-free (CH3 NH3 )2 MnCl4 single crystal was grown successfully with diverse crystal morphologies from two different solutions. This material could be excited by light in different wavelength bands. The main peak in its emission spectrum is located at 608 nm and the full width at half maximum (FWHM) is 72 nm. Furthermore, we prepared an LED using the (CH3 NH3 )2 MnCl4 single crystal, which exhibited good luminescence properties, emitting obvious red light with a QE of 2.4% upon excitation at 417 nm and used for white light illumination.